Kesalahan Ejaan Iklan Layanan Masyarakat pada Laman Web Kementerian Pemberdayaan Perempuan dan Perlindungan Anak RI - Utami, Hanifah Nur; Indriastuti, Selvia Trisna; Widyaningrum, Winda Dani (UIN Raden Mas Said Surakarta, Indonesia, 2022)
The problem raised in this research is language errors, especially in the field of spelling and sentences on the Ministry of Women's Empowerment and Child Protection website. The objectives achieved in this study were to describe writing errors in public service advertisements based on the General Guidelines for Indonesian Spelling (PUEBI), as well as describing errors in writing punctuation on public service pages based on the General Guidelines for Indonesian Spelling (PUEBI). The research method used in this study is a descriptive research method. Based on the discussion that has been analyzed, it was found that 7 advertisements were analyzed for errors from the writing of words in Public Service Advertisements on the website of the Ministry of Women's Empowerment and Child Protection of the Republic of Indonesia. These word errors include: (1) capital letter errors, as many as six data, (2) spelling errors such as one data colon error, (3) three data omission errors, (4) three data errors writing of words that are not in accordance with KBBI as much as one data, (5) errors in combining words that have main words as much as five data, (6) errors in sentences that are not effective as much as two data, (7) errors in the use of periods, commas, etc., as many as five records. thus this research can describe any errors in the Indonesian language that are found in public service advertisements on the website of the Ministry of Women's Empowerment and Child Protection of the Republic of Indonesia. Masalah yang diangkat dalam penelitian ini adalah kesalahan kebahasaan, khususnya dalam bidang ejaan dan kalimat pada Laman web Kementerian Pemberdayaan Perempuan dan Perlindungan Anak. Tujuan yang ingin dicapai dalam penelitian ini adalah mendeskripsikan kesalahan penulisan kata pada iklan layanan masyarakat berdasarkan Pedoman Umum Ejaan Bahasa Indonesia (PUEBI), serta mendeskripsikan kesalahan penulisan tanda baca pada laman layanan masyarakat berdasarkan Pedoman Umum Ejaan Bahasa Indonesia (PUEBI). Metode penelitian yang digunakan pada kajian ini adalah metode penelitian deskriptif. Berdasarkan pembahasan yang telah dianalisis, ditemukan 7 kesalahan dari penulisan kata dalam Iklan Layanan Masyarakat pada Laman web Kementerian Pemberdayaan Perempuan dan Perlindungan Anak RI. Kesalahan-kesalahan kata tersebut antara lain: (1) kesalahan penggunaan huruf kapital, sebanyak enam data, (2) kesalahan pada ejaan seperti kesalahan penggunaan tanda titik dua sebanyak satu data, (3) kesalahan penghilangan kata hubung tiga data, (4) kesalahan penulisan kata yang tidak sesuai dengan KBBI sebanyak satu data, (5) kesalahan pada penggabungan kata yang memiliki induk kata sebanyak lima data, (6) kesalahan kalimat tidak efektif sebanyak dua data, (7) kesalahan penggunaan tanda titik, koma, sebanyak lima data. Dengan demikian penelitian ini dapat mendeskripsikan bentuk kesalahan berbahasa Indonesia yang terdapat pada iklan layanan masyarakat di Laman web Kementerian Pemberdayaan Perempuan dan Perlindungan Anak RI.